Rhodium(III)‐Catalyzed ortho‐Heteroarylation of Phenols through Internal Oxidative CH Activation: Rapid Screening of Single‐Molecular White‐Light‐Emitting Materials. Issue 47 (25th September 2015) - Li, Bijin; Lan, Jingbo; Wu, Di; You, Jingsong
Abstract: Reported herein is the first example of a transition‐metal‐catalyzed internal oxidative CH/CH cross‐coupling between two (hetero)arenes through a traceless oxidation directing strategy. Without the requirement of an external metal oxidant, a wide range of phenols, including phenol‐containing natural products, can undergo the coupling with azoles to assemble a large library of highly functionalized 2‐(2‐hydroxyphenyl)azoles. The route provides an opportunity to rapidly screen white‐light‐emitting materials. As illustrative examples, two bis(triphenylamine)‐bearing 2‐(2‐hydroxyphenyl)oxazoles, which are difficult to access otherwise, exhibit bright white‐light emission, high quantum yield, and thermal stability. Also presented is the first example of the white‐light emission, in a single excited‐state intramolecular proton transfer system, of 2‐(2‐hydroxyphenyl)azoles, thus highlighting the charm of CH activation in the discovery of new organic optoelectronic materials. Abstract : White out : A rhodium(III)‐catalyzed CH/CH cross‐coupling of phenols with azoles has been accomplished to construct highly functionalized 2‐(2‐hydroxyphenyl)azoles through a traceless oxidation directing strategy. The method presents an opportunity to rapidly screen white‐light‐emitting molecules. TPA=triphenylamine substituent.